Slope risk assessment using GIS technique: study area - section U10 Shah Alam, Selangor / Shamiruddin Mahammad Azami - Mahammad Azami, Shamiruddin (2009)
There are many factors that cause slope failures such as rock mass discontinuities, weathering, mass stratification, water seepage, surface cover and erosion. The existing legislations and guidelines on residential development either on or near hilly terrain are defective to produce an acceptable and reasonable safety measures. The aim of this study is to innovate a georisk management system which is capable of mitigating risk to life and economic loss due to slope failures. The main objectives of this research are, firstly to identify and determine slope risk rating parameters. Secondly to produce georisk map for the selected site as case study and finally produce Real Time Georisk Slope Management System (RTG-SMS) using GIS technique. Most practitioners still prefer and are accustomed to conventional approach of slope stability analysis which is inadequate to guarantee zero risk to slope failure. A comprehensive literature study concluded that none of the previous studies in Malaysia focused on the consequences of the risk elements due to slope hazards such as residential areas and public roads. Therefore, this study proceed the alternative solution through three phases of methodologies: (i) literature review, (ii) produce georisk map, (iii) develop Real Time Georisk Slope Management System (RTG-SMS). This study focuses on the general physical of sedimentary ground formation and slope rating system approach modified from Slope Management and Risk Tracking (SMART). However, comparison studies with other slope rating systems do not constrain with this study. This study has also revealed that residents in Section UID, Shah Alam were almost exposed to slope failures. Through RTG-SMS, Section UID, Shah Alam requires further monitoring and proper slopes management bound to the residential area in the near future to prevent any loss of life and property damages. This study successfully proved that RTG-SMS is a useful system to be used for slope maintenance and suitable for engineers, planners, geologist and local authorities to determine the safety level of the slope. The system created also can be used to monitor the existing, current or future hilly terrain development areas which absolutely will benefit the local authorities as a decision maker supporter to approve any future hilly terrain developments that have been proposed.